Gene expression, immunohistochemical and microarchitectural evaluation of bone formation around two implant surfaces placed in bone defects filled or not with bone substitute material - Trento, Guilherme dos Santos [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Frigerio, Paula Buzo [UNESP]; Farnezi Bassi, Ana Paula [UNESP]; Okamoto, Roberta [UNESP]; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Springer, 2020)
Objective The aim of this study is to evaluate through gene expression, immunohistochemical and microtomographic (micro-CT) analysis the response of peri-implant bone tissue around titanium implants with different surface treatments, placed in bone defects filled or not with bone substitute materials. In addition, to investigate the hypothesis that porous-hydrophilic surface induces a faster bone formation. Materials and methods Twenty-six animals were divided into two groups according to implant surface treatment. In each tibia, a bone defect was created followed by the placement of one implant. On the left tibia, the defect was filled with blood clot (BC), and on the right tibia, the defect was filled with biphasic hydroxyapatite/beta-tricalcium-phosphate (HA/TCP) generating four subgroups: BC-N: bone defect filled with blood clot and porous surface titanium implant installed; BC-A: bone defect filled with blood clot and porous-hydrophilic surface titanium implant installed; HA/TCP-N: bone defect filled with bone substitute material and porous surface titanium implant installed; and HA/TCP-A: bone defect filled with bone substitute material and porous-hydrophilic surface titanium implant installed. The animals were submitted to euthanasia at 15, 30, and 60 days after implant installation. The expression of two genes was evaluated: RUNX2 and BSP. Immunohistochemical analyses were performed for detection of RUNX2, OPN, OCN, OPG, and RANKL antibodies and bone matrix proteins. Finally, four parameters were chosen for micro-CT analysis: trabecular number, separation and thickness, and connectivity density. Results Descriptive analysis showed similar findings among the experimental groups. Moreover, porous-hydrophilic surfaces presented a higher expression of RUNX2, which is probably an indicative of better osteogenesis; although the data from this study may be considered an insufficient support for a concrete statement. Conclusion Porous hydrophilic surface can improve and accelerate protein expression and bone formation.
Keywords: Osseointegrated dental implantation; Bone grafting; Cell viability